Pengaruh Bauran Pemasaran dan Kualitas Produk terhadap Keputusan Pembelian Bawang Merah di Pasar Gelugur Kota Rantauprapat Kabupaten Labuhanbatu - Tami Rahmantia; Rizki Syahputra; Praida Hansyah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to determine the influence of marketing mix and product quality on purchase decisions of shallots at Gelugur Market, Rantauprapat City, Labuhanbatu Regency. This research is an associative study using a descriptive quantitative approach. Data were collected through questionnaires distributed to 96 respondents, who are consumers of shallots at the research location. The data collection techniques used were questionnaire distribution and observation, and the data were analyzed using SPSS version 20.The results of the study indicate that the marketing mix and product quality variables have a positive and significant influence, both partially and simultaneously, on purchase decisions. Thus, it can be concluded that the marketing mix and product quality collectively have a significant effect on consumer purchase decisions of shallots at Gelugur Market.